2020
DOI: 10.1177/1559325820949797
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Quercetin and Melatonin in the Down-Regulation of HIF-1α, HSP-70 and VEGF Pathways in Rat’s Kidneys Induced by Hypoxic Stress

Abstract: Hypoxia may lead to inflammatory responses by numerous signaling pathways. This investigation intended to inspect the defensive role of Quercetin (Quer) and/ or Melatonin (Mel) against reno toxicity induced by Sodium nitrite (Sod ntr). Sod ntr injection significantly decreased blood hemoglobin concentration (Hb) with a concurrent increase in serum tumor necrosis factor- α, interleukin-6, C-reactive protein, creatinine, and urea levels. Over protein-expression of vascular endothelial growth factor and heat shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Specifically, with the development of industrial technology and the progress of science and technology, the damage of chemical raw materials to the kidney has grown immensely prominent. Data from animal models have shown that the protective effect of quercetin is closely related to the clearance of free radicals and reduction of lipid peroxidation in both industrial chemical raw materials and heavy metal and diesel particulate pollution (Li et al, 2016b;Qi et al, 2017;Uthra et al, 2017;Alshanwani et al, 2020;Morsi et al, 2022). Moreover, Quercetin was also found to reduce organophosphorus pesticide mixture-induced nephrotoxicity by regulating fatty acid, energy and sex hormone metabolism, protecting antioxidant defense systems and reducing DNA damage (Qi et al, 2017).…”
Section: Quercetin In Traditional Herbal Medicinesmentioning
confidence: 99%
“…Specifically, with the development of industrial technology and the progress of science and technology, the damage of chemical raw materials to the kidney has grown immensely prominent. Data from animal models have shown that the protective effect of quercetin is closely related to the clearance of free radicals and reduction of lipid peroxidation in both industrial chemical raw materials and heavy metal and diesel particulate pollution (Li et al, 2016b;Qi et al, 2017;Uthra et al, 2017;Alshanwani et al, 2020;Morsi et al, 2022). Moreover, Quercetin was also found to reduce organophosphorus pesticide mixture-induced nephrotoxicity by regulating fatty acid, energy and sex hormone metabolism, protecting antioxidant defense systems and reducing DNA damage (Qi et al, 2017).…”
Section: Quercetin In Traditional Herbal Medicinesmentioning
confidence: 99%
“…Quercetin has therapeutic potential in cases of renal damage [91,92]. Previous studies have concluded that quercetin may effectively treat renal injury caused by chemical compounds that induce hypoxia [30,32,93,94]. In the present study, we used quercetin as a natural agent to reduce indomethacin-induced renal injury.…”
Section: Discussionmentioning
confidence: 96%
“…Giving exogenous MT at the same time of the day can trigger physiological and behavioral rhythms (such as body temperature and rest-activity cycles) [ 80 ]. According to previous reports, MT can regulate a variety of biological functions, including the vision, neuroendocrine, reproduction, neuroimmunity, and vascular physiology [ 13 , 81 84 ]. Since the MT secretion is proportional to the night length, MT also presents a regular seasonal change cycle.…”
Section: Mt and Ovarian Functionsmentioning
confidence: 99%